Rhopalocera of the Museum Entomological Laboratory, University of Tolima (Lepidoptera: Papilionoidea - Quimbayo-Díaz, Sebastián; Moreno-Carmona, Manuela; Tafur-Acosta, Andrea Paola; Andrade-C., Miguel Gonzalo; Canal, Nelson A. (SHILAP Revista de lepidopterología, 2023)
Biological collections play an important role in the knowledge of biodiversity because they are primary sources of information. Lepidoptera are a megadiverse order and Colombia is one of the countries with the highest diversity of this taxon with approximately 3,642 species (Rhopalocera) registered so far. The objective of this work was to carry out the conservation of specimens of Rhopalocera deposited in the Entomology Laboratory Museum of the University of Tolima, which were identified and systematized. In addition, the temporal value, geographic coverage, organizational profile, health index and management priorities of the MEN- UT, in which this group of insects were carried out. A total of 695 individuals belonging to 229 species, 137 genera, 20 subfamilies and six families were identified, from nine states, where 95.54% of the records correspond to Tolima. The most abundant species in the collection were Danaus gilippus (Cramer, 1775) followed by Heliconius eleuchia (Hewitson, 1854). Regarding the organizational profile, there is a high percentage of specimens between the fifth and sixth level; the health index also shows a high number of individuals at level five. Thirty individuals with more than 50 years in the collection and 21 new records for the state of Tolima were recorded. These results reinforce the importance of biological collections for the conservation and knowledge of the country’s diversity.